Dog erythrocyte antigen 1: mode of inheritance and initial characterization. (20th August 2015) - Polak, Klaudia; Acierno, Michelle M.; Raj, Karthik; Mizukami, Keijiro; Siegel, Don L.; Giger, Urs
Abstract : Background: The dog erythrocyte antigen (DEA) 1 blood group system remains poorly defined. Objectives: The purpose of the study was to determine the DEA 1 mode of inheritance and to characterize the DEA 1 antigen and alloantibodies. Animals: Canine research colony families, clinic canine patients, and DEA 1.2+ blood bank dogs were studied. Methods: Canine blood was typed by flow cytometry and immunochromatographic strips using anti‐DEA 1 monoclonal antibodies. Gel column experiments with polyclonal and immunoblotting with monoclonal anti‐DEA 1 antibodies were performed to analyze select samples. Cross‐reactivity of human typing reagents against canine RBC and one monoclonal anti‐DEA 1 antibody against human RBC panels was assessed. Results: Typing of 12 families comprising 144 dogs indicated an autosomal dominant inheritance with ≥ 4 alleles: DEA 1− (0) and DEA 1+ weak (1+), intermediate (2+), and strong (3+ and 4+). Samples from 6 dogs previously typed as DEA 1.2+ were typed as DEA 1+ or DEA 1− using monoclonal antibodies. Human typing reagents produced varied reactions in tube agglutination experiments against DEA 1+ and DEA 1− RBC. Polypeptide bands were not detected on immunoblots using a monoclonal anti‐DEA 1 antibody, therefore the anti‐DEA 1 antibody may be specific for conformational epitopes lost during processing. Conclusions: The autosomal dominant inheritance of DEA 1 with ≥ 4 alleles indicates a complex blood group system; the antigenicity of each DEA 1+ type will need to be determined. The biochemical nature of the DEA 1 antigen(s) appears different from human blood group systems tested.